2018
DOI: 10.1373/clinchem.2017.280685
|View full text |Cite
|
Sign up to set email alerts
|

Allele-Specific Droplet Digital PCR Combined with a Next-Generation Sequencing-Based Algorithm for Diagnostic Copy Number Analysis in Genes with High Homology: Proof of Concept Using Stereocilin

Abstract: NGS-based CNV detection followed by allele-specific ddPCR confirmatory testing is a reliable and affordable approach for copy number analysis in medically relevant genes with homology issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…This type of genetic change cannot be identified using a nucleotide variant detection assay and would require a secondary screening assay. 48…”
Section: Incorporating Genetic Screening Into the Nbhsmentioning
confidence: 99%
“…This type of genetic change cannot be identified using a nucleotide variant detection assay and would require a secondary screening assay. 48…”
Section: Incorporating Genetic Screening Into the Nbhsmentioning
confidence: 99%
“…G-banded chromosome analysis of the chorionic villus sample indicated a normal female karyotype; however, prenatal CMA testing (4x180K CGH + SNP; Agilent Technologies, Santa Clara, CA) detected an apparently homozygous 33.7 kb deletion of chromosome 15q15.3 that included CATSPER2 [reported as arr[GRCh37] 15q15.3(43916972_43950720)x0] (Figure 1). The homozygous loss of CATSPER2 was confirmed by a higher density microarray (244K, Agilent Technologies) and ddPCR (Amr et al, 2018) at intron 7 and exon 7 of CATSPER2; however, parental CMA testing and ddPCR at introns 25 and 23 of STRC indicated that the paternal chromosome 15q15.3 deletion included STRC whereas the maternal chromosome 15q15.3 deletion was inconclusive at the 5' region of STRC due to the absence of copy number probes from exons 1 to intron 22 of STRC and ~6.0 kb upstream of the transcription start site. Due to these inconclusive maternal results, accurate counseling about potential hearing loss in the child could not be provided at that time.…”
Section: To the Editormentioning
confidence: 95%
“…Droplet digital PCR (ddPCR) was performed as previously described 12,13 . Given the sequence homology in exons 26 of the C4A and C4B genes, a specific assay (C4BEx26) was designed and optimized to target unique nucleotides in the C4B gene.…”
Section: Droplet Digital Pcr (Ddpcr) and The C4b Assaymentioning
confidence: 99%